Revolutionizing pig farming: Japan’s technological innovations and environmental strategies for sustainability. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This review examines Japan’s pig farming landscape, highlighting key barriers while exploring projects that foster large-scale sustainable development efforts by emphasizing precision technologies integration and policy implications. Materials and Methods: A literature review was conducted using keyword searches across Google Scholar, covering studies published between 2018 and 2024. The review encompassed studies on Japan’s pig farming, addressing prospects, production metrics, challenges, consumption patterns, market trends, precision technologies, and insights from peer-reviewed journals, credible websites, government reports, and conference proceedings. Results: Japan, one of Asia’s largest pork consumers, relies on imports, with domestic production covering only 47.08% of consumption, highlighting a need for greater efficiency. Although small-scale farms continue to dominate the pig industry, the sector is navigating a pivotal shift toward modernization and the expansion of large-scale operations. Farmers face mounting pressures from feed costs, labor shortages, diseases, and strict environmental regulations. Precision pig farming technologies address these by optimizing resource use, enabling early disease detection to reduce costs, improving herd health to promote better welfare, and managing manure to reduce emissions. Conclusion: Integrating large-scale operations with precision pig farming technologies can redefine Japanese pig farming, promoting animal welfare and environmental sustainability. The government must secure financial backing (partial or full subsidies) to support large-scale operations, tax reductions on imported tools, and grants to foster domestic tools and renewable energy innovations to achieve this. Future life-cycle assessment research will be essential for evaluating the long-term environmental impacts, ensuring viability, and promoting sustainability in Japan’s pork production sector.J. Adv. Vet. Anim. Res., 12(2): 454–476, June 2025http://doi.org/10.5455/javar.2025.l912